Entrepreneurship Education as a Catalyst for Women's Economic Empowerment - Asmayanti Asmayanti; Pahrul Pahrul; Mahmuddin Mahmuddin; Andi Anggi Kemalasari; Hasisa Haruna (Jurnal Sipakatau: Inovasi Pengabdian Masyarakat, 2025)
Women's Economic Empowerment is crucial in supporting the Sustainable Development Goals. One aspect of women's economic empowerment that has been widely studied is women's involvement in entrepreneurial activities. Women have great potential to develop businesses. However, they often face barriers such as a lack of management education, access to capital, building business networks, and the persistence of community understanding that causes gender discrimination that women are not obliged to earn a living. This assumption can be an obstacle to the growth of the nation's economy. One of the efforts to overcome this is to educate the community on the importance of women's economic empowerment through Entrepreneurship Education. The purpose of entrepreneurship education for women is to encourage the national economy and improve family welfare. Economically empowered women can play a positive role in meeting personal needs, family and social activities.